THE LEGAL CERTAINTY OF CERTIFIED LAND WITHOUT OFFICIAL LAND DEED (PPAT) DOCUMENT IN PADANG JAYA SUB DISTRICT OF BENGKULU UTARA REGENCY - Erwin Setyawan; Farida Fitriyah; Emelia Kontesa (Universitas Bengkulu, 2020)
This study aims to analyze and indentify the causes and factors affecting as well as the effect of Sales and Purchase of certified Land without Official Land Deed (PPAT) document in Padang Jaya sub district of Bengkulu Utara Regency. The research method used in this study was qualitative descriptive. Data collecting technique was empirical data from interview that have been conducted on September 13th to 20th, 2016. Data analysis used qualitative descriptive. The result of this study showed that the registration of land is not effective yet. The effective law in land registration depends on legal factor, law enforcement factor, infrastructures and facilities factor, society factor and cultural factor. While the factors affecting in implementation of law effectivity are constitutional factor and infrastructures and facilities factor. Overall it can be concluded that there is not law effectivity in Sales and Purchases of certified Land without PPAT document in Padang Jaya sub district of Bengkulu Utara Regency which needs legal protection and legal certainty in land registration.